A Mechanism for Mobile Data Offloading to Wireless Mesh Networks - Pathania, Shubham; Saini, Jatinder Singh (International Journal of Computer Sciences and Engineering, 2020)
Wireless communications at its core is all about convenience – making it easy to apply a wide variety of network typologies quickly, easily, and cost-effectively. We often think of wireless in terms of a mobile device talking to a base station or access point – the point-to-multipoint topology, plus handoff between cells. And, normally, the interconnections between those cells use wire or perhaps a different form of point-to-point wireless. Suppose instead that the required interconnect was implemented as a form of relay, with one cell simply redirecting traffic wirelessly to the next, making it possible to implement almost any configuration; that’s the domain of the wireless mesh. In this research a mechanism on mobile data offloading using wireless mesh networks is performed. In which one source node is connected with a sink node or we can say base station for communication. When there is a traffic in between the communication then the source node can change their base station or sink node. This mechanism is shown in further results.